The Influence of Principal Leadership and School Climate on Junior High School Teacher Performance - Aprilianda, Rini; Permana, Johar; Rahyasih, Yayah (Pedagogi: Jurnal Ilmu Pendidikan, 2024)
This research was conducted based on the fact that there is a school located in isolated area with high performance teacher. Teacher performance influenced by school environment, the way principal lead, work motivation, and incentive. The purpose of this research is generally carried out to determine the influence of principal leadership and school climate on teacher performance. Specifically, this research aims to describe the reason of these variables can affect teacher performance. The method of this research was a quantitative, which used quantitative descriptive method to describe the result. The data was collected by 26 teachers at SMP YPPK Santo Don Bosco Fak Fak. The data collection techniques used were questionnaires and data validation as a review to see the validity of the data. The results of the study obtained data, and it’s indicated that (1) principal leadership has a significant role in improving teacher performance, (2) school climate has significant effect on teacher performance, and (3) principal leadership and work motivation have a synergistic effect on teacher performance at SMP YPPK Santo Don Bosco Fak Fak.